2011
DOI: 10.1177/0021934710385549
|View full text |Cite
|
Sign up to set email alerts
|

The Legacy of Fear: Is Fear Impacting Fatal and Non-Fatal Drowning of African American Children?

Abstract: African American children’s rates for fatal and non-fatal drowning events are alarmingly elevated, with some age groups having three times the rate as compared to White peers. Adequate swimming skills are considered a protective agent toward the prevention of drowning, but marginalized youth report limited swimming ability. This research examined minority children’s and parents/caregivers’ fear of drowning as a possible variable associated with limited swimming ability. Results confirmed that there were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 18 publications
4
18
0
Order By: Relevance
“…Also, this current analysis showed that the greater the degree of fear, the more participation rates for swimming dropped as did self-reported swimming competence, which reinforced earlier findings (Irwin et al, 2011;Irwin et al, 2010). This result clearly is connected with how the parent/caregiver exposes or does not expose their child to swimming.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, this current analysis showed that the greater the degree of fear, the more participation rates for swimming dropped as did self-reported swimming competence, which reinforced earlier findings (Irwin et al, 2011;Irwin et al, 2010). This result clearly is connected with how the parent/caregiver exposes or does not expose their child to swimming.…”
Section: Discussionsupporting
confidence: 90%
“…Minimal changes were made to the survey. The modified questionnaire was designed in collaboration with representatives from USA Swimming; this panel of representatives was comprised of adolescent research experts, aquatic specialists, and consultants from the CDC (Irwin et al, 2009a;Irwin et al, 2009b;Irwin et al, 2011). A pilot study of 100 respondents, ages 12-17 years, was conducted to determine evidence for content/ face validity for the newly-modified survey instrument.…”
Section: Survey Developmentmentioning
confidence: 99%
“…The New Zealand Youth Water Safety Survey reported similar findings with over half of the participants reporting that they could not swim more than 100 m, and Pasifika and Asian students reporting poor competency (Moran, 2009). Similar differences in swimming skill among young people of different ethnicities have also been previously reported in Canada (Golob, Giles & Rich, 2013) and in the United States (Irwin et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…In such cases, the adults seemed to pass their fear of water on to their children. This finding supported the work of Irwin, Irwin, Ryan, and Drayer (2011) which recognized a "legacy of fear" which serves to greatly inhibit swim participation of children with parents who were fearful of water. Boston mom, Karmen, recognized this phenomenon, stating, "A lot of parents are scared and afraid so they make their kids afraid or they don't feel comfortable taking their kids to a pool."…”
Section: Cultural Constraints To Swimming Aptitudesupporting
confidence: 80%